Psychological Well-Being To Individuals Living Own - Putri Nova Sari. P (Journal Basic Science and Technology, 2020)
As a human, we are made to live together with other people. Because of human from birth until death, have a need to get intimate relationship with other human. To get a good relationship with other people, we should do interaction with other people as often as we can and do it every day. That thing maybe little bit hard to do if somebody lived alone in her house in a long time. Beside of need to get intimate relationship is unsatisfied, human can feel loneliness. Human who feel loneliness is difficult to feel happy, feel worry, inferiority and shame on other. This research was conducted to see the description of psychological well- being in individual who live alone. The approach used in this research is qualitative with qualitative research methodology. Data obtained through interviews and observations that explore six dimensions of psychological well- being, that is autonomy, environmental mastery, personal growth, positive relations with others, purpose of life and self acceptance. Participant in this research is one person who lived alone in 20 years. Technique of sampling is using theory-based on sampling / operational construct sampling. The result show that person have a positive psychological well-being.